Childbirth care profile in a usual risk maternity hospital: type of delivery and interventions (Research, Society and Development, 2020)
The objective of the research was to identify the profile of childbirth care in a usual risk maternity hospital in the centre of the Brazilian state of Rio Grande do Sul.  This is a cross-sectional study that investigated the labour’s duration, the use of technologies, the type of delivery and interventions. Data are from a patient record book in the approximate period of 7 months of the year 2017, composing a total of 485 birth deliveries analyzed from IBM SPSS version 23 software. A cross-table was made, applying the Qui-square test and identifying the statistically significant differences, with results with value p